A comparison of gravimetric geoid models over Western Australia, computed using modified forms of Stokes's Integral - Featherstone, Will (Royal Society of Western Australia, 1999)
Gravimetric models of the geoid over Western Australia have been constructed using two adapted forms of Stokes's integral; one uses the unmodified Stokes kernel and the other uses a deterministically modified kernel. These solutions use a combination of the complete expansion of the EGM96 global geopotential model with Australian gravity and terrain data. The resulting combined solutions for the geoid are compared with the control given by Global Positioning System (GPS) and Australian Height Datum heights at 63 points over Western Australia. The improved fit of the model that uses a modification to Stokes's kernel indicates that this approach is more appropriate for gravimetric geoid computations over Western Australia.